2007
DOI: 10.1109/robot.2007.363569
|View full text |Cite
|
Sign up to set email alerts
|

Image-Based Visual Servoing of the I4R parallel robot without Proprioceptive Sensors

Abstract: This paper proposes a method to control an I4R parallel robot by the observation of its legs with a calibrated camera. We show that the control law depends only on the edges of its forearms extracted from the image and that no proprioceptive sensors are used. Indeed, the variables needed for control (namely, the directions of the arms and forearms as well as the positions of the wrists ) can be reconstructed from the forearms edges. Experimental validation of the reconstruction is given and simulation of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…We would like to point out that this estimation is performed in a single image. Note that this result was already verified in [13] on a real I4R robot, and is adapted here for the end-effector of the Quattro robot.…”
Section: B Estimation Of Attachment Pointssupporting
confidence: 69%
“…We would like to point out that this estimation is performed in a single image. Note that this result was already verified in [13] on a real I4R robot, and is adapted here for the end-effector of the Quattro robot.…”
Section: B Estimation Of Attachment Pointssupporting
confidence: 69%
“…Another research topic is to design dynamic vision-based control laws that take into account and compensate for more dynamic phenomena such as flexibilities, backlashes and other mechanical defects. Considering parallel robot control problem, it appears that it is also relevant to control this class of robots from leg observation (Dallej et al 2007;Özgür et al 2011). One interesting perspective is thus to generalize this concept into dynamic control of a parallel robot from leg observation.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown in ref. [48] that these parameters can be measured using only vision in the case of the I4R robot. Moreover, it was shown that one can get rid of the joint values in the same movement.…”
Section: The Length Of the Referent Element [A 1imentioning
confidence: 99%